Kebebasan Manusia dalam Predestinasi Ganda John Calvin berdasarkan Institutes of the Christian Religion - Christian Arisandi Kiding Allo (Sekolah Tinggi Filsafat Seminari Pineleng, 2023)
This article focuses on John Calvin’s double predestination which is often considered to close the space for human freedom. It is said to be double because for Calvin God not only chooses those who are saved, but also actively chooses those who are rejected. The problem that arises is that humans are rejected and cursed because of their sins. This way of thinking implies that humans sin based on their freedom. Therefore, the relationship between God’s sovereign determination and human freedom to sin is the main focus of this study. An analytical descriptive approach will be taken on the theme of double predestination in Institutes and freedom in the philosophical tradition to clarify the relationship between humans and determinism. This description produces a perspective to see the space of human freedom in God’s absolute sovereignty.